HUBUNGAN ANTARA PRODUK KALSIUM X FOSFAT SERUM DENGAN PENYAKIT ARTERI PERIFER PADA PASIEN HEMODIALISIS REGULER DI RSUP SANGLAH DENPASAR - Wulandari, Dewi Catur; Raka Widiana, I G; SL, Jodi; Sudhana, I W; Suwitra, Ketut (journal of internal medicine, 2012)
Peripheral Arterial Occlusive Disease (PAOD) is common among patients undergoing hemodialysis (HD). In the general population, DM, male, cigarette smoking, advanced age, hypertension and dyslipidemia are the most important risk factors for PAOD. Recently, some studies in patients with regular HD found evidences that PAOD associated with increase of calcium and phosphate serum level and increase of Ca.P product due to secondary hyperparatiroidism. A cross-sectional study was done on 46 regular HD patients to evaluate prevalence of PAOD among patients who are undergoing regular HD and their association between Ca.P product. Morning fasting plasma were taken for lipid profile, blood sugar, blood urea nitrogen, serum creatinin, albumin level, Ca, inorganic P. Ankle-brachial index (ABI) of blood pressure as measured after dialysis session using Va-Sera VS-100. Fourty six (26 males, 20 females) regular HD patients, age 50.95 ± 9.90 years, duration of HD 27.7 ± 22 months were included in this study. Using ABI < 0.9 as cut off value for the presence of PAOD, 15.2% had PAOD. Means of Ca serum level was 9.04 ± 0.76 mg/dl, phosphate serum level was 56.48 ± 23.90 mg/dl. Using 55 or more as cut off value for abnormal concentration of Ca.P product, 47.7% patients had abnormal Ca.P product. Three of 21 patients with Ca.P 55 had PAOD and 4 of 23 patients with Ca.P < 55 had PAOD ( OR 0.79 with 95% CI : 0.15 ? 4.04 for patients with Ca.P < 55 ). Using logistic regression to control Ca and P levels, Ca.P 55 tend to associate with increased risk of PAOD (OR 6.22 ; 95% CI : 0.23 ? 167.71) More than fifteen percent of patients with regular HD had PAOD. More than fourty seven percent of patients had abnormal Ca.P. Patients with Ca.P 55 tend to associated with increased risk of PAOD (OR 6.22 ; 95% CI : 0.23 ? 167.71)
Keywords: peripheral arterial occlusive disease, ankle brachial index, calcium phosphate product